The interaction of flotation reagents with metal ions in mineral surfaces: A perspective from coordination chemistry - Chen, Jianhua (Minerals engineering, 2021)
[Display omitted] •Metal ions semi-constrained in surface show very different properties from solution metal ions.•The interaction of regent molecules with metal ions in surface belongs to hetero-coordination.•Spin state and polarizability of metal ions in surface determine the properties of bonding with reagents.•Unoccupied π orbitals of a depressant molecule play an important role in its depressing power.•CFSE enhances the stability of reagents adsorbing on surface. The selective interaction between reagents and mineral surfaces is the core basis of mineral flotation separation. This paper creatively proposes a perspective from coordination chemistry to clarify the interaction mechanism of reagents with mineral surfaces systematically and profoundly. The metal ion in mineral surface is far different from the free ion. The former is in a semi-constrained state, causing the properties of surface metal ions to be greatly affected by surface structures and properties of surrounding atoms. Based on coordination chemistry, the π-backbonding model is advanced for the interaction between sulfhydryl collectors and sulphide minerals. It is of interest that with more π electron pairs, the surface metal ion is more likely to interact with sulfhydryl collectors containing unoccupied π orbitals; with greater polarizability, the metal ion is more prone to covalent interactions with sulfhydryl collectors. In addition, the unoccupied orbitals play a crucial role in selectivity of depressants. For example, the depressants NaCN and Ca(OH)+ containing unoccupied π orbitals can strongly depress pyrite holding π electron pairs, but can hardly depress galena possessing no π electron pair. Furthermore, the crystal field stabilization energy resulting from the interaction between reagents and surface metal ions can influence the stability of reagent adsorption, and can adequately explain the order of flotation critical pH for sulphide minerals. The coordination theory sheds new light on the interaction mechanism between flotation reagents and mineral surfaces.